Peran SAMPAN Kalimantan dalam Konservasi Mangrove di Kalimantan Barat - Suratiningsih, Dewi; Hardilina, Hardilina; Nugarahaningsih, Nurfitri (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research aims to describe the role of SAMPAN Kalimantan as an NGO that contributes to the preservation of mangrove ecosystems as an effort to adapt to climate change. This research uses a qualitative descriptive research methodology with data processing using source triangulation. In addition, researchers used the theory of the role of non-governmental organizations (NGOs) to analyze the role of SAMPAN Kalimantan in mangrove conservation. The results of this research are that SAMPAN Kalimantan, which runs the program in Kubu Raya, has begun to fulfill its role as an NGO, namely as Executor/Implementer, Catalyst and Partner. As the Executor, it is known that there are several activities carried out by the community that can benefit the general public and provide employment opportunities and benefits for the local community by utilizing existing natural resources, one of which is the potential for fish, shrimp and crabs. As a catalyst, SAMPAN Kalimantan has encouraged areas that have not received permits to become social forestry since 2013.